Pengaruh Pembiayaan Mudharabah, Musyarakah, Murabahah Terhadap Profitabilitas pada BRI Syariah Di Indonesia (Studi Empiris Pada BRI Syariah di Indonesia Tahun 2011-2014) - Kristanto, Bagas Alif; , Drs. Eko Sugiyanto M.Si (2016)
Intention of this research is to check and test influence of defrayal of Mudharabah, Musyarakah, and Murabahah to Profitability at BRI Syariah in Indonesia year of 2011-2014. This research to used quantitative descriptive method by using secondary data in the form of defrayal data, profit before tax and total asset of company of banking at 2011-2014 period. Amount of sample cover publicized report continuously from year of 2011 until 2014 and financial statement owning equipment of data pursuant to accurate variable which taken by purposive sampling. Analyzer test used covering of doubled linear regression, classic assumption test, and hypothesis test covering coefficient determines R2 test, F test, and t test. Pursuant to the result of data analysis can be concluded that factors influencing profitability covering defrayal of Mudharabah Musyarakah and. Murabahah Where all the independent variable have an effect on significant to profitability, this matter shown by p value of each variable < 0,05. So that hypothesis of H1 H2 and H3 can be having effect.